Human papillomavirus infection and p16 overexpression in oropharyngeal squamous cell carcinoma: a case series from 2010 to 2014. (August 2015) - Donà, Maria Gabriella; Spriano, Giuseppe; Pichi, Barbara; Rollo, Francesca; Laquintana, Valentina; Covello, Renato; Pellini, Raul; Giuliani, Massimo; Pescarmona, Edoardo; Benevolo, Maria
Aim: Human papillomavirus (HPV) associated oropharyngeal squamous cell carcinomas (OPSCC) show better prognosis and response to therapy. We evaluated HPV-DNA prevalence, p16 overexpression and HPV-attributable fraction in recent consecutive OPSCCs.Materials & methods: 140 OPSCCs were analyzed for HPV-DNA using the INNO-LiPA assay and p16 overexpression using CINtec ® Histology kit.Results: HPV-DNA prevalence was 40.7%, and was significantly higher in basaloid and nonkeratinizing SCCs, but similar in tonsillar and base of tongue SCCs. Moreover, 98.0% of the HPV-positive OPSCCs overexpressed p16, compared with 12.3% of the HPV-negative cases (p < 0.0001). Based on HPV-DNA and p16 double positivity, 39.8% of the cases were HPV related.Conclusion: The high estimate of the HPV-attributable fraction suggests that a substantial proportion of OPSCC patients may be managed less intensively.